Summary of international energy research and development activities, 1974-1976. (National Technical Information Service, U.S. Dept. of Commerce, 1977)
Summary of International Energy Research and Development Activities 1974–1976 is a directory of energy research and development projects conducted in various countries such as Canada, Italy, Germany, France, Sweden, and the United Kingdom between 1974 and 1976. A limited number of projects sponsored by international organizations such as the International Atomic Energy Agency are also included. This directory consists of nine chapters and opens with a section on organic sources of energy such as coal, oil and gas, peat, hydrocarbons, and non-fossil organic sources. The next sections focus on thermonuclear energy and plasma physics; fission sources and energy production; geophysical energy sources; conversion technology; and environmental aspects of energy conversion and use. Energy transport, transmission, utilization, and conservation are also covered. The final chapter deals with energy systems and other energy-related research on subjects ranging from car sharing and urban passenger transport to nuclear power plants, energy supply and demand models, and high-power molecular lasers. This monograph will be a valuable resource of information for those involved in energy research and development.--Provided by publisher.